PREPARATION OF LECTURERS FOR RESEARCH-BASED LEARNING: EUROPEAN EXPERIENCE - Oksana Bulvinska (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article deals with preparation of lecturers for research-based teaching in the framework of professional development programs at European universities. It has been noted that the development of professional competencies among lecturers, necessary for such teaching, is determined by 2 factors: the orientation of the institutional policy and corporate culture of a higher educational institution towards the introduction of a holistic system of teaching based on research, as well as professional development programs at university aimed at improvement of existing professional competencies and acquisition of the new ones. The article analyzes the experience of University College London (UK) and the University of Gohenheim (Germany) in preparation of lecturers for research-based teaching. It has been confirmed that these higher educational institutions have implemented a holistic research-based teaching system, as well as extensive professional development programs for lectures to prepare them for such teaching, including not only trainings, but also individual consultations and seminars, mentoring support from more experienced colleagues, manuals, scientific resources, online directories, etc. The article presents actual examples of introduction by lecturers of a holistic research-based teaching system into the educational process at all educational levels.